Perceptions of professional role in community mental health nurses: The interplay of power relations between nurses and mentally ill individuals - Karanikola, Maria; Kaikoushi, Katerina; Doulougeri, Karolina; Zafiropoulou-Koutrouba, Anna; Papathanassoglou, Elizabeth (My University, 2018)
Nurses’ professional role perception is related to the quality and safety of care. Limited data exist regarding professional role perception in community mental health nurses (CMHNs). The aim of the present study was to investigate the living experience of Greek-Cypriot CMHNs of their professional role. A phenomenological approach based on Munhall's methodology was applied. According to purposive sampling, five Greek-Cypriot CMHNs participated, following informed consent. The interplay of power relations between participants and mentally ill individuals during CMHNs’ house calls was revealed as the core theme contributing to the perception of their status within their professional role. Participants’ perception of their status as visitors in patients’ homes rather than authoritative figures, an image held within hospital mental health services, was deemed as the greatest challenge of their professional role. Moreover, the necessity for autonomous and rapid decision-making during home visits was described as an absolute prerequisite for professional effectiveness. Overall, the main themes were grouped as follows: professional role perceptions, perception of self within professional role, feelings and expectations about professional role. Non-power relations between participants and patients, along with efficacy, control and adequate clinical autonomy for effective professional practice were highlighted as major prerequisites during house calls. Interventions towards nurses’ psychosocial and organizational empowerment, as well as strengthening patients’ self-determination are proposed.
Keywords: Autonomy; Community; Guest; Power relations; Psychiatric nurses